Multitasking Media, Persepsi Penggunaan Media untuk Keluarga, dan Kendala Penggunaannya - Satrio Dwi Ananda; Herman Dwi Surjono (Postgraduate, University of Mataram, 2023)
The occurrence of social changes to the use of technology in everyday life makes multitasking media behavior increasingly potential for families. The use of these media raises various perceptions and assessments. This study aims to understand the behavior of multitasking media in parents as an initial information base for applying technology in parenting programs. This study describes the types of media, time of use, differences in media behaviour and perceptions of parents, barriers to the use of technology during parenting learning to the relationship between the number of barriers and perceptions of media use for families in parents. The research method used is quantitative descriptive and correlational. The subjects of this study were determined by purposive sampling technique, with the number of participants as many as 63 parents. This study found that 17.4% of parents were classified as heavy media multitaskers (HMM), 39.7% were classified as medium media multitaskers (MMM), and 42.9% of parents were classified as mild media multitaskers. Print media and television use for parents is relatively high and evenly distributed in computers, music, social media, browsing, and SMS. The duration of media use by parents is still dominated by 1 hour to 4 hours. There is no difference between mother and father with the Sig value (2-tailed)> 0.05, namely 0.087 and 0.084. This study also found that the perception of media use for parents to learn parenting was still moderate. The obstacles in using the media for parenting activities are the number of advertisements that appear, harmful internet content, invalid and reliable information obtained, poor website appearance, confusing content, connection disruption, unfriendly users, no accessible applications offline, no media support, perception of time-consuming that much until the information is too general, and can’t directly ask if learning is done online. However, these obstacles are separate from the perception of media use in parents